2020
DOI: 10.1177/0040517520934507
|View full text |Cite
|
Sign up to set email alerts
|

Degradation study of polyester fiber in swimming pool water

Abstract: The disinfection of swimming pool water is vital to maintain water quality. The chemicals used in this practice can damage the fabrics of bathing suits and shorten the shelf life of the textile substrate. The degradation of polyester, a polymer that is widely used in bathing suits for swimming pools, was investigated. For this, a 23 factorial design was employed for the experimental methodology. The effect of several variables was analyzed in a simulated swimming pool batch, such as textile-exposure time, conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
1
11
0
2
Order By: Relevance
“…Additional analysis of a large set of microscopic images taken on different segments of the aged materials revealed that the surface deterioration is more pronounced after outdoor aging, i.e., after additional exposure to direct sunlight. This result is in agreement with the results attributed to photodegradation by Nguyen-Tri [ 5 ] and chemicals used for disinfecting by Cianek [ 11 ], which also showed surface damage to PET fibers. The observed fibrillation on the material surface is expected to have a negative impact on the tactile comfort of the material and to facilitate the pilling.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Additional analysis of a large set of microscopic images taken on different segments of the aged materials revealed that the surface deterioration is more pronounced after outdoor aging, i.e., after additional exposure to direct sunlight. This result is in agreement with the results attributed to photodegradation by Nguyen-Tri [ 5 ] and chemicals used for disinfecting by Cianek [ 11 ], which also showed surface damage to PET fibers. The observed fibrillation on the material surface is expected to have a negative impact on the tactile comfort of the material and to facilitate the pilling.…”
Section: Resultssupporting
confidence: 91%
“…FTIR analysis showed that the reactions that take place during the degradation process involve the breaking of the polymer chains. Morphological analysis of SEM has shown a decrease in the average diameter of PET samples [ 11 ]. In addition to PA and PET, the third polymer fiber used in swimsuits is polyurethane elastane fiber (Spandex), which is used for its stretchability.…”
Section: Introductionmentioning
confidence: 99%
“…Figure S2A–D shows the typical examples of white and red shirts (C-1; C-7). Cionek et al observed stretch marks and grooves in the longitudinal view for disinfectant-treated PET fabrics . Sorensen et al observed holes and pitting on the surface of UV-degraded PET fibers .…”
Section: Resultsmentioning
confidence: 99%
“…However, polyesters can be degraded under aqueous conditions . Many studies have been conducted on changes in fabrics and fibers; notably, alkaline conditions, , ultraviolet light, thermal treatment, and disinfectants are harmful to polyesters. Considering real crime situations, fiber specimens found in crime scenes are not necessarily fibers removed from unused or new fabrics but particularly from used fabrics.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 30–50 litres of fresh water are required for dyeing a kilogram of polyester textile. 46 Owing to our dependence on polyester textiles for coordination with the latest fashions, there is no doubt that a series of severe environmental problems would result from the production of polyester textiles as well as their waste treatment. 710…”
mentioning
confidence: 99%